2021
DOI: 10.1371/journal.pone.0248200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous alpha-tocopherol on physio-biochemical attributes and agronomic performance of lentil (Lens culinaris Medik.) under drought stress

Abstract: Water being a vital part of cell protoplasm plays a significant role in sustaining life on earth; however, drastic changes in climatic conditions lead to limiting the availability of water and causing other environmental adversities. α-tocopherol being a powerful antioxidant, protects lipid membranes from the drastic effects of oxidative stress by deactivating singlet oxygen, reducing superoxide radicals, and terminating lipid peroxidation by reducing fatty acyl peroxy radicals under drought stress conditions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 63 publications
7
25
0
2
Order By: Relevance
“…The maximum growth rate was found at 30 °C, and the minimum was found at 5 °C. These findings are consistent with several previous studies [ 23 , 26 , 34 , 48 , 53 , 54 ]. According to them, agronomic parameters are affected significantly by T and Ψ , and when the Ψ becomes more negative, both the rate and percentage of germination decrease (if they do not become completely inhibited) due to the water deficit [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The maximum growth rate was found at 30 °C, and the minimum was found at 5 °C. These findings are consistent with several previous studies [ 23 , 26 , 34 , 48 , 53 , 54 ]. According to them, agronomic parameters are affected significantly by T and Ψ , and when the Ψ becomes more negative, both the rate and percentage of germination decrease (if they do not become completely inhibited) due to the water deficit [ 55 , 56 ].…”
Section: Discussionsupporting
confidence: 94%
“…The results of our study showed that increasing temperatures within the range of 20-30 • C resulted in an increase of 95% in germination, and the lowest value displayed a 25% decrease at 5 and 20 • C (~10 • C). The maximum growth rate was found at 30 • C, and the minimum was found at 5 • C. These findings are consistent with several previous studies [23,26,34,48,53,54]. According to them, agronomic parameters are affected significantly by T and Ψ, and when the Ψ becomes more negative, both the rate and percentage of germination decrease (if they do not become completely inhibited) due to the water deficit [55,56].…”
Section: Discussionsupporting
confidence: 92%
“…In response to high temperature and drought stress, the concentrations of soluble sugars increased in almost all of the genotypes examined in our study. Our results are consistent with the ndings of Shah et al 41 who discovered a signi cant increase in soluble sugar content and proline content in lentil cultivars exposed to water de cit stress conditions. In lentil, Sehgal et al 26 reported similar results, showing a signi cant increase in soluble sugars in response to heat and drought stresses.…”
Section: Discussionsupporting
confidence: 93%
“…The highest theoretical CVG value will be obtained when all sown seeds germinated on the first day. This was calculated from the formula suggested by Shah et al [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The earth’s climate is changing drastically in recent decades and these climate changes affect all the physiological phases of plant growth and development [ 12 ]. This changing climate increases the intensity and frequency of the abiotic factors that contrarily reduced agricultural production [ 13 ].…”
Section: Introductionmentioning
confidence: 99%